FIRM CHARACTERISTICS AND DISCLOSURE OF MATERIALITYASSESSMENT IN SUSTAINABILITY REPORTS - Eriandani, Rizky; Evangelia, Adventia (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2024)
This research aims to examine the influence of financial performance, leverage, corporate governance, dan company size on the level of disclosure of materiality assessments in sustainability reports published by 177 public business entities in Indonesia in the 2020-2022 period, yielding a total of 531 firm-year observation. The variables used are the scoring results from content analysis of sustainability report (MDISC), return on asset ratio (ROA), market to book ratio (MTB), debt to equity ratio (DER), audit committee size (ACSIZE), number of independent commissioners (INDBOD), and the natural logarithm of total assets (SIZE) which are tested using ordinal logistic regression. The results show that ROA, MTB, ACSIZE and SIZE have influence on the level of disclosure of materiality assessments, while DER and the INDBOD have no effect. This research findings are useful for business entities and regulators in order to develop quality in sustainability reporting practices to increase transparency and accountability.